Supramolecular associations peculiar to coordination complexes - Tiekink, Edward R. T. * (2017)
In order to achieve the ultimate goal of crystal engineering, the deliberate and rational design of the molecular packing in crystals, a thorough understanding of the way molecules self-assemble in the condensed phase is required. A particular favourite mode of assembling molecules, for both organic compounds and coordination complexes, relies on conventional hydrogen-bonding; halogen bonding is increasingly being recognised as being able to provide reliable supramolecular synthons. The formation of dative/coordinate bonds between donor bases and metal centres is a hugely important mode of selfassociation of coordination complexes, often leading to the ubiquitous coordination polymers/metal-organic frameworks. The aim of this presentation is to explore other modes of supramolecular assembly pertaining to coordination complexes exclusively. For example, it turns out that chelate rings can participate in supramolecular synthons much in the same way as arene rings do. Thus, chelate rings may assemble via stacking interactions of the type (chelate)…(chelate) resembling (arene)…(arene) interactions, and they can function as acceptors in C–H…(chelate) interactions akin to C–H…(arene) contacts. A survey of these, and more, will be presented to highlight the supramolecular assemblies they sustain along with theoretical considerations to explain the nature of the supramolecular association and the energies of stabilisation they impart to the molecular packing.